Nghiên cứu tổng hợp và khảo sát hoạt tính xúc tác của cobaltetrasulfophthalocyanine trên chất mang TiO2 - Minh, Lê Thanh; Thảo, Phan Thanh; Tân, Lê Minh (Vietnam Journal of Chemistry, 2014)
Cobalt-tetrasulfophthalocyanine supported on TiO2 carrier has been synthesized. Investigate of oxidising sulfide by using the supported catalyst was carried out as well. The result shows that the activity of the catalyst is highest under visible light irradiation and is carried out at the pH of 10.